2002
DOI: 10.1191/1460408602ta241oa
|View full text |Cite
|
Sign up to set email alerts
|

The role of hypertonic saline dextran in trauma resuscitation

Abstract: AM Perera and KM PorterModern trauma management has recognized the importance of using conserva-tive¯uid resuscitation regimes in order to prevent complications from¯uid overload arising. Hypertonic/hyperoncotic¯uids appear to provide an ideal means of facilitating this, requiring only small volumes to rapidly elevate blood pressure. Hypertonic saline dextran (HSD) was introduced in 1985 but its take up has been slow, a large part of this has been due to the lack of human trials and concerns about complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 116 publications
(131 reference statements)
0
4
0
Order By: Relevance
“…Similar symptoms occurred with the infusion of HS-dextran (50). Tissue damage caused by extravasation has been documented and intravenous line patency must be assured before infusion (51).…”
Section: Problems Associated With Administrationmentioning
confidence: 79%
“…Similar symptoms occurred with the infusion of HS-dextran (50). Tissue damage caused by extravasation has been documented and intravenous line patency must be assured before infusion (51).…”
Section: Problems Associated With Administrationmentioning
confidence: 79%
“…dextran and hypertonic saline) 64 have immunomodulatory effects. Here, many lessons can be learned from critically ill patients (Appendix page 7).…”
Section: Clinical Mitigation Strategiesmentioning
confidence: 99%
“…Perera and Porter 12 reviewed the use of hypertonic saline dextran and its generally positive effects on neutrophil activation and cytokine activity, but concluded that ‘ a well-constructed UK study is needed before large scale usage could be recommended ’ which is of course still awaited.…”
Section: The Immunology Of Trauma/coagulopathymentioning
confidence: 99%